Worker adaptation and workplace accommodations after the onset of an illness - Jan Høgelund; Anders Holm (IZA Journal of Labor Policy, 2014)
Workers who become work-incapacitated may try to change employer or stay with their current employer in an accommodated job. We study the effect of these strategies on sick-listed workers' employment durations. We use survey and register data of 809 workers. We simultaneously estimate the duration until returning to work and the duration of employment using the timing-of-event approach. We find that workplace accommodations increase employment durations with the current employer. We also find that workers returning to work with a new employer have significantly shorter employment durations than workers returning to work with the current employer (with or without accommodations).
Keywords: I12; J21; J28; J64; 330; Sick leave; Workplace accommodation; Employment duration; Hazard rate model